Development of Realistic Mathematics Education Mobile Learning in Elementary School (Universitas Negeri Semarang, 2019)
The research is motivated by the lack of ICT-based learning media, mathematics learning for elementary school children is still inductive, and lacks of good character attitudes. The purpose of this study was to develop realistic mathematics education mobile learning for elementary school students. The research method used ADDIE (Analyze, Design, Develop, Implement, and Evaluate). Based on the needs analysis, both students and teachers need a realistic learning media that can be represented through smartphone or tablet devices to support the learning. So, it is important to develop realistic mathematics education mobile learning. The product was validated by media experts, material experts, and practitioners. The results of expert validation get percentage of 90% with very good category for its performance, 92.5% with very good category for the content competency. Furthermore, validation results from practitioners get 89% with very good categories. The realistic mathematics education mobile learning contains elements used in context, used of models, interactivity, students contribution, and interwoven. In addition, the media contained concrete images, videos, sounds, and questions that are arranged in online system. Based on these results it can be said that the realistic mathematics education mobile learning is valid for use.